2012
DOI: 10.1519/jsc.0b013e31825d81ba
|View full text |Cite
|
Sign up to set email alerts
|

IGF-I, IGFBPs, and Inflammatory Cytokine Responses During Gender-Integrated Israeli Army Basic Combat Training

Abstract: Insulin-like growth factor 1 (IGF-I) is a robust metabolic and anabolic biomarker that has been demonstrated to be reflective of military training-induced body composition changes and influenced by initial aerobic fitness level. Greater mechanistic insight into the IGF-I response to physical training can potentially be gleaned by also examining other regulatory factors that influence IGF-I biological activity (i.e., insulin-like growth factor-binding proteins [IGFBPs] and inflammatory cytokine responses). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
24
1

Year Published

2012
2012
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 19 publications
5
24
1
Order By: Relevance
“…In the present study, no significant differences in the IL-6 concentrations were observed during the study period due to large individual variation. Chester et al (2013) and Nindl et al (2012) have also reported similar findings previously. Gomez-Merino et al (2002) and McClung et al (2013) have found, however, increases in the IL-6 concentrations during prolonged MFT.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…In the present study, no significant differences in the IL-6 concentrations were observed during the study period due to large individual variation. Chester et al (2013) and Nindl et al (2012) have also reported similar findings previously. Gomez-Merino et al (2002) and McClung et al (2013) have found, however, increases in the IL-6 concentrations during prolonged MFT.…”
Section: Discussionsupporting
confidence: 86%
“…IL-6 has been shown to remain unchanged (Chester et al 2013) or increase (Gomez-Merino et al 2003;McLung et al 2013) during MFT. No changes in IL-6 concentrations were observed during Israeli army basic training (Nindl et al 2012). However, these studies did not report the associations between IL-6 concentration and physical performance of warfighters.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations